PENGARUH KOMPOS LIMBAH BAGLOG JAMUR TIRAM DAN PUPUK HAYATI TERHADAP PERTUMBUHAN DAN HASIL TANAMAN CABAI KERITING (Capsicum annum L.) PADA TANAH GAMBUT PEDALAMAN (Effect of Compos Waste Baglog Oyster Mushrooms t and Biofertilizers on Growth and Yield of Curly Chilli (Capsicum annum L.) on Peat Soil) - T. M. T, Sinaga; S, Winarti; K. V., Asie, K. V. (AGRIPEAT, 2015)
ABSTRACTThe objectives of this study namely analyze of waste baglog of effect oyster mushrooms compost togrowth and yield curly chilli on Peat Land and to find out the doses of waste baglog of oystermushrooms compost which give the best curly chilli growth and yield. The experimental design usedwas a completely randomized design factorial (CRD), which consists of two factors treatments. Thefirst factor was giving the waste baglog of oyster mushrooms compost which consists of four levels,namely: control, 100, 200 and 300 gpolybag-1. The second factor was giving the biofertilizer whichconsists of three levels, namely: control, 40 and 60 gpolybag-1.The results showed that the interactionwaste compost baglog oyster mushrooms and biofertilizer only be obtained at the age of two weeksafter planting the plant height chilli curls and composting waste baglog oyster mushrooms verysignificant effect on plant height, stem diameter, days to flowering plants, productive branches, theamount of fruit and fresh weight per plant. Composting 100 g polybag-1 is the best dosage.Biofertilizer application significantly higher only in the high growth of curly chilli plants.Keywords: Curly Chilli, Waste Baglog of Oyster Mushrooms Compost, Biofertilizer, Peat Land.